Student Sport, Mass Sport and Sport of High Achievements (Journal of Pedagogical Inventions and Practices, 2022)
The article reveals the meaning of the concept of "mass sport". It will focus on the differences and similarities of mass sports with high-performance sports, as well as the goals and objectives pursued by this current direction of the sports movement